Penerapan Model Pembelajaran Snowball Throwing dalam Meningkatkan Hasil Belajar Siswa Kelas IV pada Mata Pelajaran BAM di UPTD SD Negeri 01 Balai Panjang - Dhea Adrianda; Wismanto Wismanto; Deprizon Deprizon; Radhiyatul Fithri; Sakban Sakban; Salman Salman (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
One of the main problems at SD Negeri 01 Balai Panjang is the learning outcomes of students in the subject of Minangkabau Natural Culture (BAM) in grade IV of elementary school. Students often have difficulty understanding conventionally taught material. Classroom Action Research (PTK) is used to improve student learning outcomes by using a snowball competition model in BAM subjects in grade IV. This research was carried out in two cycles, with four stages of planning, implementation, observation, and reflection. The results showed a significant increase in several aspects: (1) an 80% increase in teacher activity during the first cycle to 86.25% in the second cycle, (2) student activity increased from 72.5% in the first cycle to 92.5% in the second cycle, and (3) student learning outcomes increased from 38.46% in the pre-cycle to 84.61% in the second cycle. These findings show that the application of the Snowball throwing learning model significantly improves student learning outcomes in BAM subjects in grade IV elementary school, as well as increases the involvement and activities of both teachers and students.